Student Well-being pada Remaja Jawa - Tri Na'imah; Tukiran Tanireja (Psikohumaniora: Jurnal Penelitian Psikologi, 2017)
Abstract: This study aims to describe the source of student well-being in Javanese adolescents. This research uses quantitative research approach and supported by qualitative. Research location in Banyumas with cluster random sampling technique. Instrument data collection using the scale of student well-being and open source questionaire student well-being and interview guide. Quantitative data analysis using descriptive. The results of the study are: 1) The sources of student well-being are the dimensions of social relations, cognitive, emotional and spiritual. 2) The inhibiting factor of achieving student well-being is if there are problems in the social, cognitive, emotional, physical and spiritual.Abstrak: Penelitian ini bertujuan untuk mendeskripsikan sumber student well-being pada remaja Jawa. Penelitian ini menggunakan pendekatan penelitian kuantitatif dan didukung dengan kualitatif. Lokasi penelitian di Banyumas dengan teknik cluster random sampling. Instrumen pengumpulan data menggunakan skala student well-being dan openquesioner sumber student well-being serta panduan wawancara. Analisis data kuantitatif menggunakan deskriptif. Hasil penelitian adalah: 1) Sumber-sumber student well-being adalah dimensi hubungan sosial, kognitif, emosi dan spiritual. 2) Faktor penghambat tercapainya student well-being adalah jika ada masalah dalam dimensi sosial, kognitif, emosi, fisik dan spiritual.